Big Data Management and NoSQL Databases - Simona-Vasilica Oprea; Adela Bara; Niculae Oprea (Ovidius University Annals: Economic Sciences Series, 2023)
In this paper, we aim to showcase the general context, characteristics of NoSQL, data management using NoSQL database and an exemplification in MongoDB. Moreover, organization and management of large volumes of data (Big Data), the trend in the field of advanced database systems and business intelligence will be depicted in this research. The large volumes of data in various fields of activity require adequate management in order to gain a competitive advantage or to achieve the quality of decisions. Various fields generate large volumes of data, such as: consumerism and home devices, smart infrastructure, security and surveillance, healthcare system, transportation, retail and industrial sectors, others.